2022
DOI: 10.1186/s12889-022-14323-1
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and willingness to accept syphilis chemoprophylaxis among men who have sex with men from three cities in China: a cross-sectional study

Abstract: Background The awareness and willingness to use doxycycline-based syphilis chemoprophylaxis among men who have sex with men (MSM) in China remain largely unknown. Methods We recruited MSM online from Nanjing, Wuhan and Changsha between August and October of 2021, collected data from online survey, analyzed their data using descriptive statistics, and constructed binary logistic regression for factors associated with awareness and willingness to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Data were collected nationwide randomly and anonymously via a professional data collection platform—Wen Juan Xing (Changsha Ranxing Information Technology Co., Ltd., Hunan, China), which is very straightforward and friendly for users (i.e., potential participants). Its validity for conducting online survey studies has been verified in previous studies ( 26 28 ). The use of human data from the surveys was carried out in an ethical manner, in line with the principles of the Declaration of Helsinki (as revised in 2013) ( 29 ).…”
Section: Methodsmentioning
confidence: 62%
“…Data were collected nationwide randomly and anonymously via a professional data collection platform—Wen Juan Xing (Changsha Ranxing Information Technology Co., Ltd., Hunan, China), which is very straightforward and friendly for users (i.e., potential participants). Its validity for conducting online survey studies has been verified in previous studies ( 26 28 ). The use of human data from the surveys was carried out in an ethical manner, in line with the principles of the Declaration of Helsinki (as revised in 2013) ( 29 ).…”
Section: Methodsmentioning
confidence: 62%
“…The residence regions were classified as four regions based on the announcement from the National Bureau of Statistics in 2021 (Table ) 23 . Seven items including sources of mpox infection, possible routes of transmission, susceptible population, clinical symptoms, vaccines, specific drugs, and preventive measures were used to assess mpox‐related knowledge based on previous studies 24,25 . To quantify mpox‐related knowledge, each correct answer received one point.…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of public health strategies among MSM, such as bacterial STI prevention using doxycycline prophylaxis, depends on community and healthcare provider acceptance for success. Several studies, primarily based on surveys or interviews, indicate that the use of doxycycline for preventing bacterial STIs is generally accepted among MSM [33][34][35][36] .…”
Section: Community Acceptabilitymentioning
confidence: 99%
“…In China, an online survey on 725 participants verified that willingness to use syphilis chemoprophylaxis was greater among those without a history of prior doxycycline use (p = 0.009). Among respondents, 67.8% preferred a post-exposure strategy, while 60.0% expressed concerns about potential side effects as their primary worry 34 . In Canada, 424 MSM completed a questionnaire during routine STI clinic visits and results showed that 60.1% and 44.1% were likely to use DoxyPEP or DoxyPrEP, respectively.…”
Section: Community Acceptabilitymentioning
confidence: 99%